0.74NaNbO3–0.26Sr(Mg1/3Nb2/3)O3 lead-free dielectric ceramics with high energy storage properties. Issue 5 (1st March 2023) - Dong, Qinpeng; Dong, Xiaoyan; Pan, Yue; Wang, Xiang; Wang, Jiaming; Nong, Peng; Xu, Mingzhao; Zeng, Dafu; Deng, Lian; Zhang, Hailin; Zhou, Huanfu; Chen, Xiuli
Abstract: Sodium niobate (NaNbO3 ) ceramics are commonly investigated for use as energy storage ceramics because of their excellent properties. NaNbO3 ceramics are modified mainly by doping with a Bi-based composite perovskite, that is, by the nonequivalent doping of Bi 3+ at the A site of the NaNbO3 ceramic. In addition, the high volatility of Bi at high temperatures increases the defects in the ceramics. This paper provides a new idea of doping modification of sodium NaNbO3 -based energy storage ceramics. Here, (1− x )NaNbO3 – x Sr(Mg1/3 Nb2/3 )O3 ( x  = 0.17, 0.20, 0.23, 0.26) ceramics were prepared by doping NaNbO3 with an Sr-based composite perovskite. Compared with Bi-based composite perovskite, Sr-based composite perovskite doping of NaNbO3 ceramics can also obtained good energy storage properties: a total energy storage density of 4.28 J/cm 3 and an energy storage efficiency of 89.3%. In addition, the ceramics exhibited good frequency stability (2–200 Hz) and a high charge/discharge rate (1.06 μs).